The match - Coben, Harlan, 1962- (2022)
Harlan Coben returns to Wilde, the man with a past shrouded in mystery who appeared one day in the Ramapo Mountains with no memory of how he got there or the mother and father who abandoned him. Wilde uncovers a major break in the case that may hold the key to revealing the truth of his origins. But the discovery links him with a present-day disappearance and presumed suicide that is much more than at first it appears.
Wilde has grown up knowing nothing of his family, and even less about his own identity. All he knows is that, as a young child, he was found living a feral existence in the Ramapo mountains of New Jersey. He became known simply as Wilde, the boy from the woods. Now Wilde has had a hit on the DNA website he has been researching. A 100% match. His father. They meet up, and Wilde soon realises that his father doesn't even know he had a son and is as mystified as Wilde is by his existence. Undaunted, Wilde continues his research for his family on DNA websites where he becomes caught up in a community of online doxxers, a secret group committed to exposing anonymous trolls. Then one by one these doxxers start to die, and it soon becomes clear that a serial killer is targeting this secret community - and that his next victim might be Wilde himself ...
Sequel to: The boy from the woods.
Keywords: Abandoned children -- Fiction; Missing persons -- Investigation -- Fiction; Fathers and sons -- Fiction; Recluses -- Fiction; Cousins -- Fiction; Fugitives from justice -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels